In-vitro and in-vivo antibacterial effect of Croton lobatus Linnaeus L. on two days post surgical wounds in rats - Kilani, MA; Hassan, AZ; Fadason, ST; Obalowu, AM; Aliyu, A; Kilani, HM Badmus (Bangladesh Journal of Scientific and Industrial Research, 2019)
Phytochemical constituents of Croton lobatus L. (C. lobatus) water extracts and quantitative analysis were carried out following standard procedures. The antibacterial activity against Staphylococcus aureus (ATCC 33591); Streptococcus Spp; Pseudomonas aeruginosa (ATCC 9028); Proteus vulgaris; Escherichia coli (ATCC 43895); and Salmonella Spp (ATCC 4932) was carried out at the concentration of 0.5g/mL, 0.05 g/mL and 0.00 5g/mL of water. In vivo antimicrobial assay was carried out by creating four wounds of 0.5 by 0.5 cm on dorsal surface of a male albino rat under anesthesia. The wounds were left for 48 hrs, after which they were accessed and samples were collected for culture, identification and colony forming unit counts (CFU). Respective treatment using dried C. lobatus, C. lobatus (water extract), Physiological saline solution and Cicatrin powder was carried out and samples were collected at day one, three, five and seven after initiation of treatments for CFU counts on nutrient and MacConkey agar. The phytochemical studies revealed that C. lobatus contains carbohydrates, glycoside, saponins, steroids, triterpenes, flavonoids, alkaloids and tannins. Croton lobatus L. showed a dose dependent activity against micro organisms with C. lobatus 0.5 inhibited the growth of most bacteria at the zone of inhibition ≤ 21mm. This was also supported by in vivo antimicrobial assay. Secondary metabolite tannins, triterpenoids, flavonoids, crotonic acids and saponin were responsible for its antimicrobial activity against the tested microorganisms thereby supporting its usage by the traditional medicine practitioner in Nigeria to treat chronic wounds. Bangladesh J. Sci. Ind. Res.54(2), 139-146, 2019